2017
DOI: 10.1007/s12182-017-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction behavior of hydrolyzed polyacrylamide/xanthan gum mixed polymer solutions

Abstract: Partially hydrolyzed polyacrylamide (HPAM) as the main component of slickwater fracturing fluid is a shear-sensitive polymer, which suffers from mechanical degradation at turbulent flow rates. Five different concentrations of HPAM as well as mixtures of polyacrylamide/ xanthan gum were prepared to investigate the possibility of improving shear stability of HPAM. Drag reduction (DR) measurements were performed in a closed flow loop. For HPAM solutions, the extent of DR increased from 30% to 67% with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 32 publications
5
45
0
Order By: Relevance
“…Following e.g. Huang & Desroches (2004); Wang et al 2018 Truncated power-law Habibpour & Clark (2017)). The limiting viscosities are the same for both models.…”
Section: The Numerical Resultsmentioning
confidence: 99%
“…Following e.g. Huang & Desroches (2004); Wang et al 2018 Truncated power-law Habibpour & Clark (2017)). The limiting viscosities are the same for both models.…”
Section: The Numerical Resultsmentioning
confidence: 99%
“…Moreover, one must bare in mind that the addition of heavy molecular weight polymer also increases the viscosity of the fracturing fluid. The resulting fluid exhibits a degree of shear thinning (Habibpour & Clark 2017) and visco-elasticity (White & Mungal 2008; Larson & Desai 2015). The increase of the (low shear rate) viscosity with polymer concentration can be estimated via the Mark–Houwing–Sakurada relation between intrinsic viscosity (where is the viscosity of the solvent, and the concentration) and molecular weight: (typically expressed in ) (Brandrup et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is proved that the degradation rate of the polymer synthesized at high temperature is faster. Habibpour and Clark [35] studied hydrolyzed polyacrylamide solutions of different concentrations. It was found Zhang et al [30] also verified Brostow's hypothesis through experiments.…”
Section: Factors Affecting the Mechanical Degradation Of Polymer Dragmentioning
confidence: 99%
“…It is proved that the degradation rate of the polymer synthesized at high temperature is faster. Habibpour and Clark [35] studied hydrolyzed polyacrylamide solutions of different concentrations. It was found that with the increase in hydrolyzed polyacrylamide concentration, the shear degradation resistance of the solution increased.…”
Section: Factors Affecting the Mechanical Degradation Of Polymer Dragmentioning
confidence: 99%